The responses of a funnel‐web weaving spider, Agelena labyrinthica, to elevated CO2 concentration. Issue 3 (8th December 2016) - Wang, Xia; Zuo, Lin; Yun, Yueli; Chen, Jian; Zhang, Zengtao; Peng, Yu
Abstract: The effects of elevated CO2 concentration on the growth and development of the funnel‐web weaving spider Agelena labyrinthica (Clerck) (Araneae: Agelenidae) were studied in climate chambers with low (370 μl l −1 ) or high (750 μl l −1 ) CO2 concentration. Seventh‐instar A. labyrinthica cultured under each of these CO2 concentrations were randomly selected to determine nutrient composition (total protein, total amino acid, and free fatty acid) and digestive or detoxification enzymes activity (peroxidase, amylase, and superoxide dismutase) using test kits. When reared under high CO2 concentration, total development of A. labyrinthica was significantly faster. Carapace length and width and body weight did not differ between CO2 concentrations, nor the levels of protein and total amino acids in seventh‐instar A. labyrinthica . However, free fatty acid levels were significantly lower under high CO2 concentration. Specific activities of peroxidase and superoxide dismutase in seventh‐instar A. labyrinthica did not differ between CO2 concentrations. The specific activity of amylase under high CO2 concentration was higher than that of the low CO2 group. The effects of elevated CO2 on A. labyrinthica varied from those on the wandering spider Pardosa astrigera L Koch, as found in an earlier study. Apparently, elevated CO2 has a species‐specific impact on spiders.